2020
DOI: 10.3390/jpm10040275
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorder and Childhood Apraxia of Speech: Early Language-Related Hallmarks across Structural MRI Study

Abstract: Autism Spectrum Disorder (ASD) and Childhood Apraxia of Speech (CAS) are developmental disorders with distinct diagnostic criteria and different epidemiology. However, a common genetic background as well as overlapping clinical features between ASD and CAS have been recently reported. To date, brain structural language-related abnormalities have been detected in both the conditions, but no study directly compared young children with ASD, CAS and typical development (TD). In the current work, we aim: (i) to tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 104 publications
1
25
0
3
Order By: Relevance
“…MRI analysis. Brain tissue segmentation was performed using FreeSurfer based on 3D T1-weighted images as in [54]. FreeSurfer is used as pre-processing workflow for structural MRI data to perform volumetric segmentation and cortical reconstruction through 31 processing steps [55].…”
Section: Plos Onementioning
confidence: 99%
“…MRI analysis. Brain tissue segmentation was performed using FreeSurfer based on 3D T1-weighted images as in [54]. FreeSurfer is used as pre-processing workflow for structural MRI data to perform volumetric segmentation and cortical reconstruction through 31 processing steps [55].…”
Section: Plos Onementioning
confidence: 99%
“…We identified that systemic injection of MCP-1-neutralizing Ab promotes a robust volume increased in the SSP and a prominent volume decreased in the CbX. ASD patients and preclinical models of ASD-like behavior exhibit a reduction of MRI-based volume in SSP [3], increased cerebellum volume [4,5], and in uncinate fasciculus overgrowth [6], a region associated with impaired socio-emotional processing. Molecular traits setting volumetric changes in brain have not been totally documented; a recent proposal suggests that systemic proinflammatory profile associates with volume reduction of cortical gray and white matter [56], and volume reduction in the lower parietal lobe in humans [57].…”
Section: Discussionmentioning
confidence: 98%
“…Autism spectrum disorder (ASD) is a neurodevelopment disease characterized by the inability to process and respond to external stimuli, atrophied verbal and non-verbal communication, disinterest in socialization, and stereotypic behaviors [1,2]. ASD subjects integrate structural abnormalities in critical regions of the central nervous system (CNS) including total volume reduction on primary somatosensory cortex [3], and an increase in cerebellum volume [4,5]. Studies employing diffusion tensor imaging (DTI)-based tractography found that individuals with ASD exhibit a uncinate fasciculus overgrowth [6], volume reduction in corpus callosum [7], as well as a decreased volume in lateral and medial orbitofrontal surface area, isthmus cingulate thickness, and an increased volume in the putamen [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Xiao et al (2017) employed a random forest classifier and utilized the regional average cortical thickness feature for ASD prediction. Similarly, Conti et al (2020) constructed a linear‐kernel SVM to explore possible ASD‐specific brain structural features, concluding that a set of cortical thickness features can achieve the best predictive performance. Previous studies indicate that autistic subjects show volume differences compared with typically developing subjects, such as smaller cerebellum volume (Rogers et al, 2013; Stoodley, 2014), larger amygdala volume (Nordahl et al, 2020), or larger hippocampus volume (Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%